PROMOTING PROSPERITY: THE ISLAMIC DEVELOPMENT BANK AND THE RISE OF ISLAMIC BANKING AND FINANCE IN CENTRAL ASIA - F. GRESH, Geoffrey (CENTRAL ASIA AND THE CAUCASUS, 2008)
Islamic banking and finance is on the rise and taking root in Central Asia. Since the collapse of the Soviet Union and formation of new nation-states in 1991, Muslim republics in the region have witnessed a significant increase in Islamic financial institutions. Moreover, Islamic banking and finance has been viewed by Islamic scholars as an innovative way for the former Soviet republics of this region to form an economic bloc with other Islamic countries outside of Central Asia, ultimately leading to a greater market advantage in a competitive global economy. One of the keys to accessing global markets is by sponsoring national and regional socioeconomic development, and liberal economic reform. The prevailing Soviet legacy in these Muslim republics, especially the notion of a centrally planned economy, has greatly hindered such development. However, with the advent of Islamic banking and finance, the Muslim republics of Central Asia and the Southern Caucasus have already experienced a significant boost in socioeconomic development that will hopefully continue long into the future. Throughout the twentieth century, Islam was an important cultural and religious outlet for the people of Central Asia despite its repression under Communist rule. As the Muslim republics of this region grow more exposed to new forces of global change, including market forces, a com-munications and information revolution, as well as radical Islam, their governments are struggling to adapt and create new political and economic structures to survive in an increasingly intercon-nected world. Under these new pressures of glo-bal change, many regional rulers have clung even stronger to their previous modes and methods of governing under a command economy and one-party political system, while other leaders have attempted to liberalize national markets in a glo-bal economy. The Soviet legacy continues to plague the modern development of most former Soviet re-publics in Central Asia, making it more complicated for the penetration of Islamic banking and finance to the region. Nevertheless, with the assistance of the Islamic Development Bank (IDB)based in Jeddah, Saudi Arabia, there has been a noteworthy increase of Islamic banking and fi-nance in the region. This article examines the important role of the IDB in promoting socioeconomic development across the region. Moreover, a majority of the Central Asian and South Caucasian republics view Islamic banking and financial institutions as important outlets through which to channel the energies of radical Islamic opposition groups. Despite witnessing moderate success in the region, the IDB has confronted significant obstacles in its promotion and development of Islamic financial institutions for regional because of the strong Soviet legacy and precarious political situations that prevail. Even with the persistence of their Soviet past, Muslim states in the region are experiencing a growth in Islamic banking and finance. In the last decade, Islamic banking and finance have become significant forces for positive change in the region. The IDB acts as an important instrument of legitimacy for the ruling elite and neo-nomenklatura of the region who continue to experience a rise in opposition from radical Islamic forces. For the purposes of this article, the rise of Islamic banking and finance will be compared among the six Muslim republics of the former Soviet Union: Azerbaijan, Kazakhstan, Uzbekistan, Turkmenistan, Tajikistan, and Kyrgyzstan. Each has incorporated Islamic banking and finance to varying degrees depending on the nature of its political system and economy in the post-Soviet era. The IDB has acted as the primary catalyst in this process of incorporation. It has most successfully entered the financial services sector of the economy in countries that have adopted more liberal economic reforms, most importantly Azerbaijan and Kazakhstan. In any case, for both of these countries it will be shown that the IDB has had to deal with the complex politics of a rentier state that have developed over the past decade due to the rise of oil and gas revenues. States are classified as rentier states when a substantial portion of the national revenue is generated from a local natural resource like oil or natural gas. In order for Islamic banking and fi-nance to take a stronger hold in these countries, a well as in other regional rentier states like Turkmenistan and Uzbekistan, it is believed that the political ruling elite must be involved in the formation and subsequent financial benefits of Islamic banking and finance.